Pengembangan Modul Praktikum Laboratorium Sekolah Tinggi Teknik Lingkungan (STTL) Mataram - Fatmalia, Enida; Nurhidayatullah, Nurhidayatullah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The purpose of this study is to find out the results of the development of practicum modules in STTL Mataram laboratories are based on a process skills approach. The procedure of practicum module development refers to the ADDIE learning development model. Data collection techniques were carried out by means of an assessment by 3 experts and limited trials on students in the even semester of the 2018/2019 academic year at D-3 Kesehatan Lingkungan of STTL Mataram with a sample of 30 people. The instruments used in this study were expert assessment questionnaire and student response questionnaire on the results of module development. Data analysis techniques use expert judgment categorization criteria, whereas limited trials use the average categorization of the results of trials using the Gutman scale calculation. The results showed that the score of expert assessment of the modules developed were (1) Module 1 semester 1 average score of 3.5 included in both categories with information can be used with a little revision; (2) Module 3 semester average score 3.5 is included in both categories with information can be used with a little revision; and (3) Module 5 semester average score 3.5 is included in both categories with information can be used with a little revision. While the limited test results show that the modules developed are included in the Good category but need to be improved and refined to be able to produce modules that are ready to be used in practicum.